Librarians and Information professional activities in Nepal during COVID - 19 Pandemic - Vaidya, Bina (Access: An International Journal of Nepal Library Association, 2022)
This article deals with librarians and information professionals including retired librarians, working librarians and all in the field of libraries during the COVID- 19 pandemic 2020 along with the brief history on professional librarians' development in Nepal. It also highlights the adopted online platform of a series of webinars dealing with current important and useful information relevant to library and information science organized by Tribhuvan University, Central Department of Library and Information Science (CDLIS). Further, the article provides a picture of the sudden changes brought by the unexpected outbreak of COVID - 19 pandemic in the library management, services and organization.